NOURICITY - Technical report on qualitative data collection (Focus Group Discussions) - Fongar, Andrea; Ekesa, Beatrice; Dijkxhoorn, Youri; Linderhof, Vincent (2020)
Poverty and malnutrition hotspots are moving from rural to urban communities, as Africa is urbanizing. The population in cities and countries are faced with the coexistence of overweight, obesity, micronutrient deficiency and undernourishment, the so-called ‘triple’ burden of malnutrition. The question is Who is affected and Why are they affected remains unclear. The project ‘NOURICITY’ seeks to answer these questions by engaging in a chain of multi-stakeholder participatory events and fieldwork meant to deliver a blueprint for partnerships seeking to improve urban nutrition in Africa. The technical report describes and identifies results and challenges of the qualitative data collection exercise to gather information around the food systems in Kanyanya parish, Kampala, Uganda.